Writing Complicity. - Lazzara, Michael J. (Radical History Review, 2016)
An essay on the civilian and writing complicity in Chile's memory narrative is presented. It talks about writer Mariana Callejas' complicity in 1976 assassination of General Carlos Prats and his wife Sophia Cuthbert. It is noted that Callejas joined the youth group Chilean Communist Youth, and supported the leftist causes against the U.S. and Vietnam. It highlights the studies that focus on the victims of the human rights violations.